No-Fault, Motor Vehicle Accidents, and The Civil Resolution Tribunal: Effective Justice or False Prophet? - Cumming, Kaitlyn (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2024)
Since May 2021, instead of using tort litigation and lawyers to determine a lump-sum amount for what a person should be compensated for after being injured in a car crash, the Insurance Corporation of British Columbia [ICBC] has shifted to a new No-Fault system that provides statutorily defined entitlement to care, recovery and income replacement benefits. Disputes over those benefits are now under the jurisdiction of the rapidly growing Civil Resolution Tribunal [CRT], an online tribunal lauded for its contribution to access to justice (A2J) as a negotiation and adjudication platform for use without lawyers for smaller and simpler civil matters. This article asks whether the combined shift to No-Fault and CRT jurisdiction effectively meets the access to justice needs of those injured in motor vehicle accidents. After surveying the institutional changes to the A2J landscape for those injured in MVAs, narratives surrounding the changes, and conducting a quantitative outcome of analysis of CRT decisions between individual claimants and ICBC where ICBC was found to be successful before the CRT in 73% of cases, this article concludes that ICBC’s new No-Fault system creates A2J concerns and significant bargaining inequalities for those injured in MVAs that are not overcome by recourse to the CRT. More broadly, this article illustrates the complexities of A2J as a relational and multi-faceted phenomenon in an era where one-dimensional metrics of cost-savings, speed, and efficiency are frequently promoted as novel A2J cures.